The Impact of the Economic Crisis on Russian and CIS Gas Markets - Pirani, S (2009)
This article presents an overview of the impact of the current world economic crisis on natural gas markets in Russia and the CIS. It will discuss two types of changes that reflect broader international trends. First are the initial consequences of the recession that was triggered by the US financial crisis of September 2008: sharp falls in gas consumption, which have produced oversupplied markets and falling prices; cuts in production and investment; and intensified competition between suppliers. Second are deep-going changes that could result over the longer term, as these impacts of the recession combine with other factors. The recovery of demand, however long it takes, will be accompanied by trends such as (i) technological advances, for instance those allowing the economic recovery of unconventional gas reserves, which could in time spread beyond the US; and (ii) changes in market structure, and particularly the increasing availability of liquefied natural gas (LNG), which will have consequences for regional markets for pipeline gas.